Perinatal factors associated with developmental defects of enamel in primary teeth: a case-control study - Patrícia Corrêa-Faria; Paulo Antônio Martins-Júnior; Raquel Gonçalves Vieira-Andrade; Leandro Silva Marques; Maria Letícia Ramos-Jorge (Sociedade Brasileira de Pesquisa Odontológica, 2013)
The present study was designed to evaluate associations between developmental defects of enamel (DDE) in the primary dentition and aspects related to mothers and preschoolers in the city of Diamantina, Brazil. A case-control study was carried out involving children aged three to five years. The case group was composed of 104 children with at least one dental surface affected by DDE. The control group comprised 105 children without DDE, matched for gender and age. The diagnosis of enamel defects was performed using the Developmental Defects of Enamel Index. Information was collected through interviews investigating socio-demographic aspects, gestation, birth weight, prematurity and breastfeeding. Simple and multiple regression analyses were performed, providing unadjusted and adjusted prevalence ratios (Poisson regression). DDE were more prevalent among children who had not been breastfed (PR = 1.57; 95% CI: 1.1-2.2) and those whose mothers were under 24 years of age at the birth of the child (PR = 1.41; 95% CI: 1.1-1.9). The prevalence of DDE in the primary dentition was higher among children who had not been breastfed and those whose mothers were under 24 years of age at the birth of the child.